A week in the life. - Tan, Timothy Jiat Meng. (2012)
“A Week in the Life” is a video game about the migrant construction workers in Singapore. Players control the life of Mohamed, whose dreams are that of a typical construction worker, struggling to achieve his aspirations and goals whilst encountering a host of obstacles. It is the artist's hopes that this game will help foster greater public awareness and appreciation for migrant construction workers -- a meeting point, perhaps, for two communities that live together, but ironically so far apart.